Investment Tax Credits and the Response of Firms - Adrian Lerche (Institute of Labor Economics (IZA), 2022)
This paper estimates the direct effects of investment tax credits on firms' production behavior and the additional indirect effects arising from agglomeration economies. Exploiting a change in tax credit rates by firm size in Germany, I find that manufacturing firms increase capital and employment, with labor demand in information and communication technology-intensive industries shifting towards college-educated workers. Using geolocation data, I show that agglomeration benefits lead to a sizable further firm production expansion with these benefits materializing within distances of 5 kilometers. Worker flows from the service sector and from non-employment, rather than between manufacturing firms, explain the employment effects.
Keywords: D22; H25; H32; J23; R11; 330; investment tax incentives; capital; labor demand; agglomeration